Waste-based consumable for hardfacing by welding: a look from the Circular Economy - Azucena Elizabeth Bernal-Gutiérrez; Carmen Isabel Ulloa-Méndez; Rodolfo Najarro-Quintero; Amado Cruz-Crespo; Lorenzo Perdomo-González; Alejandro Duffus-Scott (Dyna)
In the present work, the obtaining of a consumable for the restore parts by welding from the perspective of the circular economy is addressed, using industrial solid residuals (slag from steel production, graphite from fragments of electrodes of arc furnaces) and agroindustrial residuals (ash from the combustion of biomass (rice husk)) and conceiving the non-generation of new solid residuals in the hardfacing process. The conceptual scheme of obtaining a sustainable consumable for hardfacing by Submerged Arc Welding (SAW) is proposed, establishing the internal symbiosis between the obtaining and application processes, as well as the symbiosis of these with external processes and the possibility of introduction to industrial practice. The obtaining of a flux based on residuals and its application in the hardfacing of pieces are experimentally validated, confirming the possibility of recycling the resulting slag.